2021
DOI: 10.3892/etm.2021.10309
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of extracellular matrix degradation and inflammation: A new team of possible biomarkers for oral squamous cell carcinoma stage

Abstract: Oral cancer represents one of the most common types of cancer worldwide, with oral squamous cell carcinoma (OSCC) being the most frequently diagnosed. Cytokines play a crucial role in inflammation, apoptosis and metastasis. Interleukin (IL)-8 promotes the direct migration of inflammatory cells. IL-6 induces tumor cell proliferation, increases expression of invasiveness and angiogenetic factors or matrix metalloproteinases (MMPs), promoting metastasis. Tissue inhibitor of metalloproteinases (TIMPs) blocks the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The immune-inflammatory system and matrix metalloproteases were previously demonstrated to be overrepresented in PeCa compared to normal penile tissues ( 10 , 43 ). In oral carcinomas, high levels of pro-inflammatory cytokines affect the TME by increasing ECM degradation via MMPs during disease progression ( 44 ). Our findings suggest that interactions between inflammation and matrix remodeling have a crucial role in penile carcinogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…The immune-inflammatory system and matrix metalloproteases were previously demonstrated to be overrepresented in PeCa compared to normal penile tissues ( 10 , 43 ). In oral carcinomas, high levels of pro-inflammatory cytokines affect the TME by increasing ECM degradation via MMPs during disease progression ( 44 ). Our findings suggest that interactions between inflammation and matrix remodeling have a crucial role in penile carcinogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the expression and activity of MMPs increase in OPMD and OSCC tissues in parallel with CD147 hyperactivation [ 18 , 19 ]. A trend opposite to that of MMPs is followed by their antagonists, such as the Tissue Inhibitors of MMPs (TIMPs), whose amounts in OSCC lesions are lower than those found in healthy oral mucosa [ 83 ] and inversely related to CD147 expression ( Table 2 ) [ 47 ].…”
Section: Cd147 and Invasive Oscc Developmentmentioning
confidence: 99%
“…It must be highlighted that the activation of NF-kB induced by CD147 results not only in the expression of inflammatory mediators but also in the synthesis of pro-invasive MMP-2 and MMP-9 ( Table 2 , Figure 1 ) [ 135 , 136 , 137 ]. Moreover, by triggering NF-kB-promoted MMPs expression, the concerted actions of CD147 and inflammatory cytokines cause the infiltration of OPMD or OSCC tissues by neutrophils and/or monocytes [ 26 , 28 , 83 ]. While neutrophils produce and release high levels of MMP-9 [ 8 , 83 ], monocytes differentiate into macrophages [ 26 ].…”
Section: Reciprocal Interaction Between Cd147 and Opmd/oscc-associate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation, apoptosis, and host resistance are mostly mediated by cytokines, which also act as signaling molecules in cell-cell interactions [15]. A recent study also reported that interleukin-6 (IL-6) and interleukin-8 (IL-8) are candidate markers for oral squamous cell carcinoma [16]. A growing body of research shows that increased CD44s, CD44v6, IL-1β, CXCL1, and CXCR2 expressions have been associated with different kinds of tumors [12,[17][18][19], but few studies have investigated those biomarkers in tumors of salivary glands.…”
Section: Introductionmentioning
confidence: 99%